Integrasi Filsafat Ilmu dalam Pengembangan Bimbingan dan Konseling: Tinjauan Literatur - Utami, Resti Dwi; Prasetya, Akhmad Fajar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Philosophy of science plays a crucial role in establishing the theoretical and practical foundations of guidance and counseling. However, studies that comprehensively integrate philosophy of science into the development of guidance and counseling remain limited. This study aims to analyze the contribution of philosophy of science to the development of guidance and counseling through a literature review. The method employed was a literature review by examining scientific articles and books relevant to the topics of philosophy of science and guidance and counseling. The analysis was conducted qualitatively by exploring the ontological, epistemological, and axiological dimensions. The findings indicate that the ontological dimension contributes to viewing counselees as holistic human beings, the epistemological dimension strengthens scientific legitimacy and counseling approaches, and the axiological dimension serves as the foundation for values and professional ethics of counselors. The integration of these three dimensions is essential in developing guidance and counseling practices that are reflective, adaptive, and relevant to contemporary challenges.